2019
DOI: 10.1117/1.jpe.9.021001
|View full text |Cite
|
Sign up to set email alerts
|

Factors affecting the stability of perovskite solar cells: a comprehensive review

Abstract: Accelerated depletion of fossil fuel, energy demands, and pollution force us to choose renewable and eco-friendly energy resources. Solar cells are considered as an efficient replacement for fossil fuel. In the family of solar cells, silicon-based solar cells and perovskite solar cells (PSC) have displayed significant power conversion efficiency (PCE). Perovskites have been investigated extensively over the past two decades, due to their advantageous properties, such as high absorption coefficient, efficient c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
23
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(23 citation statements)
references
References 234 publications
(313 reference statements)
0
23
0
Order By: Relevance
“…Improvements of power conversion efficiency have been the main driver for research (and publication rates) so far and the focus on solving the stability problem started later, with first reliable and detailed results about stability published as late as 2013 [8]. Nevertheless, in the past five years, the importance of stability has been emphasized and identified as the main problem to solve for the perovskite solar cells to be able to compete in the market arena [9]. This conviction has led to an increasing number of reports including data about stability and the lifetime of devices, although in very different testing conditions.…”
Section: Introductionmentioning
confidence: 99%
“…Improvements of power conversion efficiency have been the main driver for research (and publication rates) so far and the focus on solving the stability problem started later, with first reliable and detailed results about stability published as late as 2013 [8]. Nevertheless, in the past five years, the importance of stability has been emphasized and identified as the main problem to solve for the perovskite solar cells to be able to compete in the market arena [9]. This conviction has led to an increasing number of reports including data about stability and the lifetime of devices, although in very different testing conditions.…”
Section: Introductionmentioning
confidence: 99%
“…A typical state-of-the-art perovskite with the highest PCE is currently being demonstrated on a small scale in the order of ~0.1 cm 2 , as presented in Figure 3a,b. Therefore, PSC small size can be significantly observed from the inverse relationships between perovskite's PCE and area due to low fill factor (FF) and solution method (i.e., spin coating) limited large cell size, as in Figure 3a (inset) [19,58,[78][79][80]. Typically, the other main factor that hinders perovskite from vast market presence is its inherent scaling instability.…”
Section: Perovskite Solar Cell Stabilitymentioning
confidence: 99%
“…Remarkably, research has already established a link between perovskite instability and every material constituent, such as intrinsic and extrinsic materials' properties and interactions, electronic states, doping, deposition methods, and device structures [18,19]. Arguably, the inherited (intrinsic) effect could have resulted from the ion migration effect [35].…”
Section: A Perovskite Intrinsic Stabilitymentioning
confidence: 99%
See 1 more Smart Citation
“…Reports have shown that, upon exposure to these external factors, PSC degrades and loses its operational stability [10]. It was found that, in the presence of water, MAPbI 3 crystal structure forms hydrates/complex with H 2 O (Equation (1)), and deforms the perovskite structure, destroying optoelectronic properties, resulting in loss of photovoltaic performance [7,11,12].…”
Section: Introductionmentioning
confidence: 99%